IMPROVING THE ECONOMIC MECHANISM OF REGIONAL ENVIRONMENTAL CONFLICT MANAGEMENT (British Journal of Global Ecology and Sustainable Development, 2022)
The region is integrated in the development of an economic mechanism for managing environmental conflictsanalysis approaches have been implemented. Tfinancial-economic, socio-legal, socio-political and administrative-state methods of collective regulation of the process of habitat use were analyzed.